(untitled) (Research, Society and Development, 2021)
Objective: to analyze scientific evidence on the knowledge of the risks of falling in hospitalized patients. Method: the method adopted was to carry out an integrative literature review - RIL, to identify and analyze evidence on falls in a hospital environment. Search platforms were used, including Lilacs, Scielo, Pubmed and Academic Google with the words "fall" "hospital" "accident by fall" "hospital fall" "patient fall" were combined both in Portuguese and in English. Articles in these two languages ​​were included, in full, in a period that covered the last 10 years and which had the theme of falling in the hospital environment. The search found 27 articles and, after applying the exclusion criteria, 12 articles were selected for further reading. Conclusion: It is important to constantly observe and assess the health team when it comes to falls, especially when the public involved is the elderly, who can use scales such as the Morse FallScale.